2004
DOI: 10.22358/jafs/70307/2004
|View full text |Cite
|
Sign up to set email alerts
|

Minerał bioplex supplementation of diets for cows affects colostrum quality and immunoglobulins in calf blood serum

Abstract: The aim of the investigations was to assess the influence of supplementation of cow rations with zinc, copper and manganese given in the form of bioplexes during the perinatal period. Colostrum ąuality and immunoglobulin level in calf serum were evaluated. Total protein and its fractions in colostrum from the first milk as well as in calves' blood serum from the 2 M and 35* day of life were determined. Additionally, the total immunoglobulin index in week 3-4 of life (Ng M) was calculated. All calves were well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The I Ig3-4 value calculated for the calves of group 4 (0.6) may be considered as only satisfactory. Similar results were described by Kinal et al (2004). Based on I Ig3-4 values, as well as on immunoglobulin class changes, we conclude that most of the calves born in this herd were influenced by FPT or PFPT of immunity and therefore started an active immune response too early.…”
Section: Colostrum Administration and Ig Coursesupporting
confidence: 85%
See 1 more Smart Citation
“…The I Ig3-4 value calculated for the calves of group 4 (0.6) may be considered as only satisfactory. Similar results were described by Kinal et al (2004). Based on I Ig3-4 values, as well as on immunoglobulin class changes, we conclude that most of the calves born in this herd were influenced by FPT or PFPT of immunity and therefore started an active immune response too early.…”
Section: Colostrum Administration and Ig Coursesupporting
confidence: 85%
“…A common opinion is that colostrum appropriate for calves should contain at least 50 g of Ig/L (Vasseur et al, 2009). Therefore, the mean colostrum Ig concentration in this herd (79.48 g/L) could be considered good compared with that in other studies in Poland (65.5 g/L in Kinal et al, 2004;63.0 g/L in Zachwieja, 1995), as well as in other countries (59.0 g/L in Abel Francisco and Quigley, 1993;48.8 g/L in Kaske et al, 2005;34.9 g/L in Kehoe et al, 2007;and 48.2 g/L in Pritchett et al, 1991). In groups 1 to 3, the rates of colostrum evaluated as very good were similar (about 9%).…”
Section: Colostrum Qualitymentioning
confidence: 79%
“…The levels of higher Igs in the organic minerals‐supplemented cows indicated that organic trace minerals such as Mn may strengthen the immunity system in the animals (Zhao et al, 2015). Likewise, improvement of blood Igs were observed in dairy cows and newborn calves treated with an organic form of a mineral supplement containing Mn compared to sulfate form (Kinal et al, 2004). According to Nayeri et al (2014), minerals may contribute to the production of Igs and improve the passive transport of Igs in ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Fe content has low bioavailability in soils due to the presence of chelating agents (Hansen and Spears, 2009), and Fe is mostly available in the ferric form, which is less bioavailable than ferrous iron or heme iron, at least in non-ruminants (Miret et al, 2003). Organically bound zinc exhibited a positive effect on increasing immunoglobulin levels in colostrum and blood serum levels (Kinal, 2005;Kinal et al, 2004), thereby increasing glucose and proteins in blood serum (Strusińska et al, 2003), and improving the productive (Kinal et al, 2005) and reproductive performance of cattle (Uchida et al, 2001).…”
Section: Introductionmentioning
confidence: 99%